Thought of Karl Marx: an introduction - Mclellan, David (London, 1984)
The thought of Karl Marx has revolutionised the political map of the world. David McLellan's book is the best and most comprehensive introduction to Marx in English and provides the basic elements for a grasp of the range and complexity of Marx's ideas. The first half is a chronological account of Marx's ideas with a minimum of biographical and historical detail. The second half is thematic and provides a concise summary of Marx's position, and extracts from the key texts on alienation,historical materialism, dialectics, labour, class, the party, the state, revolution and future communist society. All sections have a comprehensive guide to further reading.
Keywords: Marxian economics